DEVELOPMENT OF A METHOD TO EVALUATE THE EFFICIENCY OF NANOSCALE ZERO-VALENT IRON (NZVI) TO DEGRADE POLLUTANTS - Giovana Arrighi Ferrari; Felipe Santana de Oliveira Cruz; Renata Pereira Lopes Moreira; Gustavo Alves Puiatti; Luiza Dumont de Miranda Moraes; André Fernando Oliveira (The Journal of Engineering and Exact Sciences)
Iron nanoparticles (nZVI) stand out in environmental remediation due to their high reactivity. However, they have low chemical stability when exposed to oxygen and water, reducing their effectiveness. The objective of this work was to develop and validate a method to evaluate the efficiency of nZVI from synthetic lots L01 and L02, from the degradation of dyes, orange and methyl violet (MO and MV). The previous degradation tests provided the best results for MO (~100% degradation, 12 min reaction, 0.5 g L-1 dose). The optimization using Factorial Planning obtained the optimal condition, CMO = 5.98 mol L-1 and DnZVI = 0.56 g L-1. The Boltzmann model fitted the results obtained (R2 = 0.993). Finally, a mathematical relationship was obtained that provided equivalent doses of L01 and L02 in relation to the Standard. The applied mathematical adjustments presented R²> 0.99 and errors <4%.